2021
DOI: 10.15587/2519-8025.2021.249714
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and methods of diagnosis of chronic kidney disease in cats: retrospective analysis (1981–2007)

Abstract: The aim: to conduct a retrospective analysis of literature sources on the pathogenesis and methods of diagnosis of chronic kidney disease in cats. Materials and methods. The research was conducted by the method of scientific literature open-source analysis: PubMed, Elsevier, electronic resources of the National Library named after V.I. Vernadsky (1981–2007). Results. Chronic kidney disease is a common reason for cat owners to go to veterinary clinics. The term “chronic kidney disease” has a broader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…In the present study, the dogs affected by hepatopathy were predominantly middle-aged to older animals, and the average age in the dogs was 6.9 ± 2.69. The ndings are in partial agreement with Morozenko et al, and Poldervaart et al, (2009) who reported the median age of dogs with hepatitis as 6 and 7.7 years, respectively [21,24]. Bex eld et al, (2012) reported the average age of chronic hepatitis in dogs as 8 years [30].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the dogs affected by hepatopathy were predominantly middle-aged to older animals, and the average age in the dogs was 6.9 ± 2.69. The ndings are in partial agreement with Morozenko et al, and Poldervaart et al, (2009) who reported the median age of dogs with hepatitis as 6 and 7.7 years, respectively [21,24]. Bex eld et al, (2012) reported the average age of chronic hepatitis in dogs as 8 years [30].…”
Section: Discussionsupporting
confidence: 85%
“…The use of histopathology is not only not possible and practical in a large population of patients, but it will be more useful for diffuse diseases when it is sampled blindly from one lobe of the liver [19]. Acute and chronic hepatitis are considered the most common liver disease in dogs and liver enzyme elevations are common ndings in these patients [20,21]. The other common and important hepatic disorder in dogs is copper-associated hepatopathy.…”
Section: Discussionmentioning
confidence: 99%